2015
DOI: 10.1515/jpm-2015-0319
|View full text |Cite
|
Sign up to set email alerts
|

Prospective risk of intrauterine death of monochorionic twins: update

Abstract: Intensive prenatal surveillance might decrease the unexpected fetal death rates after 33 week's gestation and our data do not support elective preterm birth for uncomplicated MCBA twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…There is a 5-fold increased risk of stillbirth among twin gestations. MCDA twins have a higher rate of stillbirth than do DCDA twins [108] . Monoamniotic twins have the highest rate of stillbirth, with rates quoted as high as 80%, primarily due to cord accidents due to entanglement in utero.…”
Section: Mortalitymentioning
confidence: 92%
“…There is a 5-fold increased risk of stillbirth among twin gestations. MCDA twins have a higher rate of stillbirth than do DCDA twins [108] . Monoamniotic twins have the highest rate of stillbirth, with rates quoted as high as 80%, primarily due to cord accidents due to entanglement in utero.…”
Section: Mortalitymentioning
confidence: 92%
“…One year later, a Portuguese study of 193 monochorionic, diamniotic twin pregnancies found that the prospective risk of fetal death after 32 weeks in women undergoing weekly fetal testing was much lower, at 1.2%. 29 One notable difference exists between these 2 studies. Namely, the first study did not employ weekly fetal testing, as did the second, but rather ultrasound examination every 2 weeks.…”
Section: Delivery Timing Considerations In Uncomplicated Monochorionimentioning
confidence: 99%
“…The Lisbon research group repeated their seminal study related to the prospective risk of intrauterine fetal death in MC twins [7]. Despite the publication of several studies on this subject, significant differences exist in recruitment and management of these sets.…”
mentioning
confidence: 99%